Anticancer Activity of Black Turtle Bean against Breast and Colorectal Adenocarcinoma: A Pre-clinical Study - Priyadarshini, R Durga; Beatrice, D Annette (Asian Journal of Biological and Life Sciences)
Black turtle bean (BTB) is a nutrient rich common bean that remain least explored and underutilized in India. Throwing light to the known and discovering unknown phytochemicals present can further help narrow focus on treating chronic diseases such as cancer and reduce disease severity. Hence, this study aimed to analyse the phytochemical profile, dietary fiber content and anti-cancer activity of BTB against cancer cell lines. Raw and cooked BTB extracts were prepared using ethanol. GC-MS analysis was carried out to identify the phytochemicals present. Dietary fiber (DF) was estimated using the AOAC official method. The anticancer activity of BTB extracts against breast adenocarcinoma (MCF-7) and colorectal adenocarcinoma (HT-29) was evaluated by MTT anti-proliferative assay. Results showed the presence of various phytochemicals predominantly comprised of flavonoids, terpenoids, steroid, fatty acids, hydrocarbon, phenol and other compounds both in raw and cooked extracts of BTB. Compounds namely quercetin, myricetin, palmitic acid, vanillyl alcohol and gallic acid were commonly present in both extracts, however the levels were found to be reduced in the cooked extract. The total dietary fiber content of raw BTB extract was 9.03±0.36 g/100g (Insouble DF-7.97±0.15 g/100g; Soluble DF- 1.06±0.09 g/100g) and of cooked BTB extract was 6.56±0.16 g/100g (Insouble DF- 5.31±0.02 g/100g; Soluble DF- 1.25±0.02 g/100g). A well pronounced anti-proliferative activity was expressed by raw BTB extract against MCF-7 cells with an IC50 of 10.25 μg/mL when compared to cooked BTB extract whose IC50 was 100 μg/mL. With respect to HT-29 cells, excellent dose-dependent inhibition was exhibited by both raw BTB extract (IC50- 4.81 μg/mL) and cooked BTB extract (IC50 - 25 μg/mL). Results of this present study emphasizes the need for further investigation to determine the phytochemicals responsible, identify potential mechanism of dietary fiber and explore pharmacological relevance
Keywords: Black turtle bean; Breast Cancer; Colorectal cancer; Dietary fiber; Phytochemicals.